From Playing To Retention: Enhancing Students’ Vocabulary Mastery Through Flashcard-Based Instruction - Faradilla Labanu; Erniwati Erniwati; Afrillia Anggreni; Zarkiani Hasyim (Journal of General Education and Humanities, 2026)
Adequate vocabulary mastery is a fundamental requirement for successful English language learning, as emphasized in the Merdeka Curriculum. However, many junior high school students still exhibit low vocabulary proficiency due to the use of monotonous and teacher-centered conventional teaching methods. Therefore, this study aimed to examine the effectiveness of flashcard-based instruction in enhancing the vocabulary mastery of seventh-grade students at SMP Negeri 1 Palu. This research employed a quasi-experimental design with two groups: an experimental group of 32 students and a control group of 32 students, selected via simple random sampling. The experimental group received vocabulary instruction using flashcards, while the control group was taught using conventional methods. Data were collected through pre-tests and post-tests focusing on students’ mastery of nouns and verbs. The results revealed a significant improvement in vocabulary mastery among students taught with flashcards compared to those taught through conventional instruction. The mean post-test score of the experimental group was 85, which was higher than the control group’s mean score of 68. Statistical analysis using SPSS version 27 showed a significance value (Asymp. Sig. 2-tailed) of 0.000, which was lower than the 0.05 significance level. These findings indicate that flashcard-based instruction has a positive and significant effect on students’ vocabulary mastery. In conclusion, the study suggests that flashcards are an effective instructional medium for improving students’ vocabulary learning, increasing motivation, and supporting retention, particularly within the Merdeka Curriculum’s emphasis on contextual and everyday-life learning. Therefore, English teachers are encouraged to integrate flashcards into vocabulary instruction to create more engaging and effective learning environments.